Literatur Review : Pengembangan Sediaan Suppositoria Dari Berbagai Ekstrak - Nailah Mutiara Wahid; Jesika Diah Pitaloka; Ria Fitriyanti Putri; Rizka Tri Amanda Hidayat; Zahratul Humaidah; Alvan Andika Permadani; Dewi Rahmawati; Dzakiya Zhihrotulwida; M. Fithrul Mubarak (CV. ITTC INDONESIA, 2026)
Suppositories are one of the pharmaceutical dosage forms administered via the rectal or vaginal route and are considered an alternative drug delivery system for patients who cannot take oral medications. The development of herbal-based suppositories has increased due to their perceived safety, minimal side effects, and diverse pharmacological activities. This study aims to review the development of suppository dosage forms based on various plant extracts through a literature review method. The method used in this study is a literature review by collecting and analyzing ten scientific articles discussing the formulation and evaluation of suppositories derived from various plant extracts such as Aloe vera, Amaranthus spinosus, Piper betle, Garcinia mangostana, Areca catechu, Peperomia pellucida, senna, Cynodon dactylon, and Cassia fistula. The analyzed parameters include formulation methods, types of bases used, physical evaluation results, and pharmacological activities. The results show that the fusion (moulding) method is the most commonly used technique in suppository preparation. The bases used include cocoa butter (oleum cacao), polyethylene glycol (PEG), and glycerinated gelatin, each influencing the physical characteristics of the suppositories such as melting point, melting time, hardness, and weight uniformity. In addition, various plant extracts demonstrate different pharmacological activities, including anti-inflammatory, antifungal, antibacterial, laxative, and anthelmintic effects. In conclusion, the development of herbal-based suppositories has significant potential as an effective and innovative drug delivery system. However, further studies, particularly stability testing and clinical trials, are required to ensure their safety and therapeutic effectiveness.